(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Obesity affects over 650 million adults worldwide, and current pharmacological treatments often have limited efficacy and adverse effects, highlighting the need for safer alternatives. Polyherbal formulations based on traditional medicines offer synergistic therapeutic benefits with reduced side effects. The present study developed and evaluated a polyherbal formulation (PHF) comprising Zingiber officinale, Allium sativum, Glycyrrhiza glabra, and Gymnema sylvestre. This formulation was prepared by using hydroalcoholic extracts obtained through maceration and was evaluated for various phytochemical studies, organoleptic parameters, etc. Following the confirmation of quality control parameters, we conducted an acute oral toxicity test in accordance with OECD guidelines. Based on this evaluation, we conclude that this polyherbal elixir formulation will be evaluated for a high-fat diet model for an anti-obesity study. HFD was given to all animals (excluding normal control) to induce obesity. PHF treatment produced a dose-dependent reduction in body weight and serum lipid parameters while normalizing liver enzyme levels compared to the HFD control group. Histopathological analysis revealed restoration of hepatic and adipose tissue architecture, supporting the biochemical findings. The observed effects suggest that the formulation exerts its anti-obesity action through modulation of lipid metabolism, inhibition of adipogenesis, and enhancement of fatty acid oxidation.